Evaluation of Vitamin D Levels According to Age, Gender and Seasonal Characteristics in Children and Adolescents - Sema Mirza; Esma Keleş Alp (Genel Tıp Dergisi, 2022)
Objective: Vitamin D is an essential hormone for the health of the musculoskeletal system and acts in immune system, cardiovascular system and metabolic homeostasis. The aim of this study was to determine the vitamin D status of children in middle region of Turkey. Also, the study evaluated the age, gender and seasonal variations in the study population. Materials and Methods: Children aged 1-17 years who were admitted to a Secondary Maternity and Children Hospital in Konya were included in this study. The medical records of the participants were retrospectively evaluated from the hospital information system between July 2016 and December 2021. All patients were categorized according to age, gender, and season in which their blood had been sampled. Results: A total of 3547 children were included in the study. The mean serum level of 25-hydroxyvitamin D in the study population was 16.45±9.39 ng/ml. The number of samples obtained in winter was 1063 (30%) and in summer 756 (21.3%), respectively. Only 7.4% (n=262) of the participants had sufficient vitamin D levels (>30 ng/ml) in the study population. Additionally, severely deficiency of serum 25-hydroxyvitamin D level was mostly measured in winter season (378 patients, 45%). Severely deficiency (352 patients, 41.9%) was most common in children aged 12-17 years. Among all patients, only 7.4% had sufficient serum 25-hydroxyvitamin D levels. Also, 5.2% (103 patients) of the girls and 3.7% (59 patients) of the boys had sufficient 25-hydroxyvitamin D levels. On the other hand, severely deficiency of serum 25-hydroxyvitamin D levels was most common in boys (521 patients, 33.1%) than in girls (137 patients, 6.9%). Conclusion: Vitamin D deficiency/insufficiency is wide spread among children in the world and in Turkey. Our study revealed that seasonal variations, age and gender affect the serum levels of 25-hydroxyvitamin D in children. In this context, the importance of vitamin D rich foods or vitamin D supplementation is increasing.